2014
DOI: 10.1096/fj.13-245472
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial and cautionary outcomes of resveratrol supplementation in pregnant nonhuman primates

Abstract: Resveratrol has been proposed as a potential therapeutic to improve metabolic health during pregnancy, yet little is known about the fetal effects of this maternal dietary supplement. We hypothesized that when administered to pregnant nonhuman primates (NHPs), resveratrol would increase uterine blood flow and mitigate the harmful consequences of maternal Western-style diet (WSD) consumption. NHPs were fed a WSD (36% fat) supplemented with 0.37% resveratrol throughout pregnancy. Outcomes were compared with coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(182 citation statements)
references
References 42 publications
10
169
1
2
Order By: Relevance
“…67 Furthermore, work in a non-human primate model has demonstrated that placental inflammation is increased with a maternal high fat diet. 71,72 Intriguingly, work in this same model has provided early evidence that the offspring microbiome is altered in association with maternal diet. 39 In this study, dams were either provided a high-fat diet or a control diet prior and during pregnancy and lactation.…”
Section: Impact Of Maternal Nutrition In Pregnancy On Offspring Gut Mmentioning
confidence: 99%
“…67 Furthermore, work in a non-human primate model has demonstrated that placental inflammation is increased with a maternal high fat diet. 71,72 Intriguingly, work in this same model has provided early evidence that the offspring microbiome is altered in association with maternal diet. 39 In this study, dams were either provided a high-fat diet or a control diet prior and during pregnancy and lactation.…”
Section: Impact Of Maternal Nutrition In Pregnancy On Offspring Gut Mmentioning
confidence: 99%
“…Although human studies have not yet assessed the safety or efficacy of resveratrol treatment during pregnancy in women consuming a WSD, our group demonstrated recently in our NHP model of WSD consumption during pregnancy that supplementation improved placental blood flow, consistent with its role in enhancing vascular function (52). However, this was accompanied by a concerning increase in total pancreas mass and proliferation and an elevation in the ␤-cell/␣-cell ratio (52). In this study, resveratrol supplementation during pregnancy resulted in a significant increase in islet vascularization, consistent with its known vasodillatory effect.…”
Section: Discussionmentioning
confidence: 80%
“…Very recently, resveratrol administered to nonhuman primates was found to exhibit several health benefits as observed from rodent studies. However, an abnormal developmental effect was found in fetal pancreas, arguing against the use of resveratrol in pregnant woman (Roberts et al 2014). Resveratrol might also interact with other dietary supplements or drugs as it inhibits human cytochrome P450 (CYP) enzymes (Baur and Sinclair 2006).…”
Section: Pharmacokinetics and Toxicitymentioning
confidence: 99%